HERG1 and CA IX expression are associated with disease recurrence in surgically resected clear cell renal carcinoma. Issue 1 (January 2020) - Lastraioli, E.; Pillozzi, S.; Mari, A.; Tellini, R.; Duranti, C.; Baldazzi, V.; Venturini, S.; Minervini, A.; Lapini, A.; Nesi, G.; Carini, M.; Arcangeli, A.
Abstract: Background: In search of novel prognostic biomarkers for clear cell renal carcinoma (ccRCC), we analysed the expression of several proteins related to angiogenesis and hypoxia. Methods: A monocentric study on 30 consecutive surgical samples from surgically-treated ccRCC patients with a 10-year follow up was performed. The following proteins were analysed by immunohistochemistry: Vascular Endothelial Growth Factor- A (VEGF-A), Platelet-Derived Growth Factor β Receptor (PDGFRβ), VEGF-receptor 1 (Flt1), VEGF-receptor 2 (KDR), Glucose Transporter 1 (GLUT1), Carbonic anhydrase IX (CA-IX) and the hERG1 potassium channel. Data were analysed in conjunction with the clinico-pathological characteristics of the patients and follow up. Results: All the proteins were expressed in the samples, with statistically significant associations of VEGF-A with PDGFRβ and Flt1 and hERG1 with CA IX. Notably, hERG1 and CAIX co-immunoprecipitated in primary ccRCC samples and survival analysis showed that the positivity for hERG1 and CA IX had a negative impact on Recurrence Free Survival (RFS) at the univariate analysis. At the multivariate analysis only hERG1 maintained its statistically significant negative impact. Conclusions: hERG1 expression can be exploited to predict recurrence in surgically-treated ccRCC patients. hERG1 channels form a multiprotein complex with the pH regulator CA IX in primary ccRCC samples their potential use as therapeutic target might be suggested.